Una técnica sencilla de distalización de caninos retenidos (2002)
ABSTRACT: Diagnosis and early treatment of impacted canines is necessary to avoid future complications that will harm dental arch integrity. Early traction of the canine involves its distalization when it is located high in the vestibule with a mesial inclination. The use of removable appliance is recommended in order to avoid secondary effects in the adjacent teeth. This type of therapy can be the only one or can be a first stage of a complex treatment depending upon patient needs.